A Water-Stable Zinc(II)-Organic framework for selective sensing of Fe3+ and Cr6+ ions. (1st August 2022) - Liu, Huimin; Ma, Zhongshu; Meng, Fansheng; Ding, Yujing; Fu, Yingqiang; Zheng, Mingyan; Yang, Jie
Graphical abstract: A flexible 3D framework [Zn3 (OH)2 (btca)2 ·2DMF]·H2 O (1) has been solvothermally synthesized by zinc nitrate salt and benzotriazole-5-carboxylic acid (H2 btca) ligand in different solvent medium. Complex 1 was structurally characterized by X-ray diffraction analysis and further identified by powder X-ray diffraction (PXRD), infrared spectra (IR), thermogravimetric analyses (TGA)elemental analyses. Single crystal structural analysis displays that complex 1 is a 3D neutral framework featuring 1D porous channels constructed by [Zn3 (OH)2 ] chains and btac linkers. Thereinto, the [Zn3 (OH)2 ] 1D chain embodies the structural characteristics of the adjacent 12-MC-4 metallacrowns, one μ3 -OH oxygen and two N atom from triazole are bonded to two metal ions in the meridional mode to produce 5-membered chelating rings. Complex 1 exhibits high water stability and pH stability in aqueous solution. This multifunctional material can be accompanied by visual reactions for selective detection of nitrobenzene, Fe 3+ and Cr 6+ anions, and can be used as a fluorescent probe. Abstract: A 3D framework [Zn3 (OH)2 (btca)2 ·2DMF]·H2 O (1) constructed by [Zn3 (OH)2 ] chains and btac 2− linkers has been solvothermally synthesized by zinc nitrate salt and benzotriazole-5-carboxylic acid (H2 btca) ligand. Powder X-ray diffraction (PXRD), infrared spectra (IR), thermogravimetric analyses (TGA), elemental analyses and x-ray crystallography validated the formula of as-synthesized 1·H2 O. Thereinto, the [Zn3 (OH)2 ] 1D chain embodies the structural characteristics of the adjacent 12-MC-4 metallacrowns, the metallacrown consists of four metals, two μ3 -OH oxygen anions and eight nitrogen atoms from triazole ligands. 1·H2 O exhibits high water stability and pH stability in aqueous solution which can be applied as a "turn–off" fluorescence probe to detect Fe 3+ and Cr 6+ ions in an aqueous solution with selectivity and sensitivity. The low cost and high yield of this work lay a foundation for the industrialization development of serum and other health testing in the future.